Ralph of the Roundhouse; Or, Bound to Become a Railroad Man - Chapman, Allen; Angell, Clare, 1874-1932 (Salt Lake City, UT : Project Gutenberg, 2012)
"Ralph of the Roundhouse; Or, Bound to Become a Railroad Man" by Allen Chapman is a novel written in the early 20th century. The story follows a young boy named Ralph Fairbanks, who is keenly interested in the railroad industry and determined to follow in his father$1 (Bs footsteps as a railroad man. The narrative sets the stage for Ralph's ambitions and introduces various characters and conflicts that will undoubtedly shape his journey. At the start of the book, Ralph is actively engaged in helping the local express agent by delivering packages from the train station in Stanley Junction. His enthusiasm for the railroad is palpable as he anticipates returning to school after his vacation. The opening scenes depict his lively interactions with railroad workers and set the groundwork for a significant turning point when he encounters a stowaway and later learns about another boy's unfortunate accident that ties into his own identity. The narrative hints at Ralph's impending transition from boyhood to more responsible endeavors, especially after a confrontation with the selfish businessman Gasper Farrington, who threatens his family$1 (Bs stability. This establishes a strong foundation for Ralph's aspirations and the challenges he will face as he seeks a place within the railroad world. (This is an automatically generated summary.)s
Release date is 2012-03-04
Produced by Al Haines
Keywords: Railroads -- Juvenile fiction